History and effects of minimum wages in Malaysia - Senasi, Vally (2014)
This paper focused on history of labor practices and wage system in Malaysia.Free market system and labor policy has changed and improved real wages since colonial era in Malaysia. Moreover, introduction of minimum wages by government is believed to impact many aspects of workers and labor system in Malaysia.Therefore, this paper then specifically analyzes the effects of minimum wages on workers in manufacturing industry in Malaysia. Prominent effects of minimum wages detected in unemployment, poverty and quality of life of developed and developing countries. However, direct impacts of minimum wage to the workers and their employers still unidentified in Malaysia. Thus, this paper interested to discuss the effect of minimum wages on labor productivity and fringe benefits of the workers and their respected employers.Labor productivity is an indicator of workers achievement in competitive world.The effects of minimum wages on worker's fringe benefits such as health insurance, training and allowances also discussed in detail.Data was gathered from survey and interviews with manufacturing workers and their employers in electrical and electronics companies in Malaysia. Malaysian Trade Union Congress (MTUC) and Malaysian Employers Federation (MEF) found to play a vital roles in setting minimum wages in Malaysia.